The cultivation of skills through the study of philosophy. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2006)
Philosophy, the mother of all sciences and knowledge, is often viewed as an extremely challenging discipline in the Arts or Humanities.